2018
DOI: 10.5194/angeo-36-1577-2018
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric geospace as displayed during the geomagnetic storm on 17 August 2001

Abstract: Abstract. Previous studies have shown that conjugate auroral features are displaced in the two hemispheres when the interplanetary magnetic field (IMF) has a transverse (Y) component. It has also been shown that a BY component is induced in the closed magnetosphere due to the asymmetric loading of magnetic flux in the lobes following asymmetric dayside reconnection when the IMF has a Y component. The magnetic field lines with azimuthally displaced footpoints map into a “banana”-shaped convection cell in one he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
(88 reference statements)
4
15
0
Order By: Relevance
“…Previous studies mainly focus on the large-scale HiLDA spots, as their high emission intensity and large size can be recognized from UV imagers onboard high-altitude satellites (Frey et al, 2003;Korth, 2004;Østgaard et al, 2018). There is one earlier study based on Viking images (on which more details can be recognized than on higher altitude global imagers such as IMAGE, however with a much reduced field-of-view) where Murphree et al (1990) shows several cases of arc-like forms separated from the dayside oval, probably detecting a HiLDA event without naming it that way.…”
Section: Observational Properties Of Hildamentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies mainly focus on the large-scale HiLDA spots, as their high emission intensity and large size can be recognized from UV imagers onboard high-altitude satellites (Frey et al, 2003;Korth, 2004;Østgaard et al, 2018). There is one earlier study based on Viking images (on which more details can be recognized than on higher altitude global imagers such as IMAGE, however with a much reduced field-of-view) where Murphree et al (1990) shows several cases of arc-like forms separated from the dayside oval, probably detecting a HiLDA event without naming it that way.…”
Section: Observational Properties Of Hildamentioning
confidence: 99%
“…HiLDA events were mostly observed in the northern hemisphere (Murphree et al, 1990;Frey et al, 2003Frey et al, , 2004Østgaard et al, 2018;Han et al, 2020). A statistical study based on the IMAGE FUV data showed that the occurrence of HiLDA in the northern hemisphere is typically connected with strong positive IMF B y , positive B z , negative B x , and low solar wind density (Frey et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have found strong evidence that lobe reconnection is more efficient in the hemisphere inclined toward the Sun, that is, the local summer hemisphere (Crooker & Rich, 1993;Frey et al, 2004;Koustov et al, 2017;Østgaard et al, 2018;Wilder et al, 2010;Yakymenko et al, 2018), from observing the sunward ionospheric convection velocity in the dayside polar cap during northward IMF. However, most studies have focused on the dependence on the solar wind electric field, E sw = v sw B T , where B T is the trans- (Koustov et al, 2017;Sundberg et al, 2009;Wilder et al, 2009;Yakymenko et al, 2018), likely to be the most important controlling factor on the lobe reconnection rate during purely northward IMF.…”
Section: Introductionmentioning
confidence: 99%